2021
DOI: 10.3389/fpls.2021.655758
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Functions of IAA-Leucine Resistant PpILR1 Provide a Genic Basis for Auxin-Ethylene Crosstalk During Peach Fruit Ripening

Abstract: Auxin and ethylene play critical roles in the ripening of peach (Prunus persica) fruit; however, the interaction between these two phytohormones is complex and not fully understood. Here, we isolated a peach ILR gene, PpILR1, which encodes an indole-3-acetic acid (IAA)-amino hydrolase. Functional analyses revealed that PpILR1 acts as a transcriptional activator of 1-amino cyclopropane-1-carboxylic acid synthase (PpACS1), and hydrolyzes auxin substrates to release free auxin. When Cys137 was changed to Ser137, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Here, we showed that TDZ reduced IAA content and transport, while induced ethylene content and signal genes in all the detected tissues ( Figure 7 , Figure 8 and Figure 10 ). Furthermore, several ILRs gene encoding the IAA-amino acid conjugate hydrolase were found to be up-regulated after TDZ treatment, which may increase the AZ sensitivity to ethylene and promote abscission [ 40 ]. Meanwhile, the increase of endogenous ethylene and the degradation of endogenous CTK can lead to the degradation of the cell wall and the separation of cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we showed that TDZ reduced IAA content and transport, while induced ethylene content and signal genes in all the detected tissues ( Figure 7 , Figure 8 and Figure 10 ). Furthermore, several ILRs gene encoding the IAA-amino acid conjugate hydrolase were found to be up-regulated after TDZ treatment, which may increase the AZ sensitivity to ethylene and promote abscission [ 40 ]. Meanwhile, the increase of endogenous ethylene and the degradation of endogenous CTK can lead to the degradation of the cell wall and the separation of cells [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ethylene-auxin crosstalk, recent reports have elucidated antagonistic effects of the two plant hormones, including auxin acting as a ripening repressor and thereby opposing the known role of ethylene in inducing ripening in tomato fruit (Su et al, 2015;Li et al, 2016). However, since the auxin-ethylene relationship is extremely intricate, some of the phenotypic effects have yet to be assigned to either phytohormone (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Treating SH peach with exogenous NAA results in increased expression of PpACS1 and a major increase in ethylene production and fruit softening ( Tatsuki et al 2018 ). Recent studies have shown that several genes coordinate auxin and ethylene signals during peach fruit ripening ( Wang et al 2021a , b , 2019a ). However, whether miRNAs are involved in the molecular mechanism of peach softening has until now remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The MF fruits soften rapidly due to high levels of ethylene ( Haji et al 2003 ). The inability of SH fruits to produce ethylene is due to the low IAA concentrations which inhibit the expression of 1-aminocyclopropane-1-carboxylic acid synthase 1 ( PpACS1 ), and the fruits maintain a degree of hardness after harvesting ( Tatsuki et al 2013 ; Pan et al 2015 ; Wang et al 2021a ). This failure of SH peaches to soften is caused by mutations of the auxin biosynthesis gene YUCCA flavin mono-oxygenase 11 ( PpYUC11 ) ( Cirilli et al 2018 ; Tatsuki et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%